Materialnoprawne aspekty orzekania kary ograniczenia wolności - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Numerous changes introduced within the criminal law have had a significant impact on the final model of the penalty of restriction of liberty. The measures adopted in 2015, following the general reform of the criminal law, have turned out to be rather ineffective. Thus, certain steps have been taken to re-model the penalty of restriction of liberty, which, to a large extent meant returning to previous solutions. This paper is primarily focused on analysing subsequent amendments within the substantive criminal law related to the penalty of restriction of liberty, with particular focus on the amendments introduced in 2016.
Keywords: penalty of restriction of liberty; electronic surveillance; community service; deduction from wages